Legal status of the actors of the experimental legal regimes (regulatory sandboxes) in Russia (Revista de Investigaciones Universidad del Quindío, 2022)
The purpose of this work is to study the legal status of actors in Russian experimental legal regimes (regulatory sandboxes). This research analyzes categories of actors of experimental legal regimes (regulatory sandboxes), as provisioned by current Russian legislation. It distinguishes two main groups of actors according to their role in experimental legal regimes (regulatory sandboxes). The research methodology is based on formal logic, systemic and structural analysis, and interpretation of legal regulations. The study distinguished two groups of actors of experimental legal regimes (regulatory sandboxes): participating actors and regulating actors. The former group includes initiators, contenders, subjects, and participants. The latter comprises regulating and authorized bodies, the business community organization, coordinating authorities, and the Bank of Russia. The research aims to determine the legal status of actors of experimental legal regimes (regulatory sandboxes), an institution previously unknown in Russia. It provides a description of subjects involved in establishing a regulatory sandbox, as provisioned by the national legislation, and makes a distinction between participating and regulating actors.
Keywords: experimental legal regimes; regulatory sandboxes; fintech; digital economy; digital innovations